Genetic Variants and Haplotype Structures in the CASC Gene Family to Predict Cancer Risk: A Bioinformatics Study - Morteza Gholami; Mohsen Asouri; Ali Asghar Ahmadi (Health Science Reports)
ABSTRACT Background and Aims The cancer susceptibility (CASC) gene family of long noncoding RNAs (lncRNAs) plays an important role in cancer. The aim of this study was to identify genetic variants and haplotype structures of CASC genes associated with cancer risk. Methods Genome‐wide association studies (GWAS) significant variants (p ≤ 5 × 10−8) on CASC family genes were identified from the GWAS Catalog‐EMBL‐EBI, and then cancer‐associated variants on CASC genes were extracted. These variants were functionally analyzed, including lncRNA:miRNA binding sites, Regulomedb scores, and eQTL. The 1000 Genome Project genotyping data Phase III were used to identify haplotypic blocks. Finally, the genes associated with them were examined for expression and gene‐gene correlation analyses using OncoDB. Results There were six haplotypic blocks in four genes. The GC, TA, and AGAC haplotypes are located in the CASC8 gene and increase the risk of prostate cancer, breast cancer, and colorectal cancer, respectively. The CA haplotype in the CASC15 gene increases the risk of neuroblastoma, AA haplotype in the CASC16 gene increases the risk of breast cancer, and ACGATG haplotype in the CASC17 gene increases the risk of prostate cancer (p ≤ 5 × 10−8). Their genes are interrelated and their expression is increased in these cancers. The rs2294214 is associated with skin cancer and has positive effects on five CASC15:miRNA binding sites. The rs3803662 is located in CASC16:miRNA binding sites, which has positive effects on hsa‐miR‐4475 and hsa‐miR‐7845‐5p and negative effects on hsa‐miR‐4524a‐3p and hsa‐miR‐4524b‐3p. Conclusion These haplotypic structures and lncRNA:miRNA:SNP interactions on CASC family lncRNAs reveal novel genetic associations between CASC genes and various cancers.